Combination of nitrogen and organic fertilizer practices increased rice yields and quality with lower CH4 emissions in a subtropical rice cropping system - Hongbao Wu; Yakang Jin; Yongjie Qi; Ruilin Huang; Fuwei Wang (Frontiers in Plant Science)
Fertilizer nitrogen (N) application has been shown to impact methane (CH4) emissions, yield and quality from rice cropping systems, yet the responses of CH4 fluxes, yield and quality to N reduction and combined application of organic fertilizer in subtropical rice cropping systems are not well documented. Six experimental treatments were conducted: N90 kg N ha-1 of urea (N1), organic fertilizer with equal N90 (O1) and 80% urea + 20% organic fertilizer (N1O1), farmer’s common practice with N270 kg N ha-1 of urea (N2), organic fertilizer with equal N270 (O2) and 80% urea + 20% organic fertilizer (N2O2) were conducted to simultaneously measure the CH4 flux, yield and quality from a subtropical rice cropping system in south China. Results showed that increased N fertilizer application significantly stimulated soil CH4 emission, increased rice yield and altered quality in paddy fields. CH4 emissions were quantified under different N fertilizer management practices in the peak rice growing season during the tillering and heading stages, respectively. Organic fertilizer alone increased CH4 emission by 442.1% in O1 and by 337.3% in O2 compared with urea. However, relative to organic fertilizer, organic fertilizer combined with urea significantly decreased CH4 emissions by 48.4% in O1 and by 39.2% in O2. Compared with N1 and N2 treatment, rice yield was significantly decreased by 34.4% and 39.5% under O1 and O2, while significantly enhanced by 49.8% and 22.3%, respectively, under N1O1 and N2O2 (P < 0.05). The protein content significantly increased under N1O1 by 18.8% and 41.5%, the amylose content by 30.3% and 14.8%, and the gel consistency by 32.7% and 15.5% in contrast to N1 and O1 (P < 0.05). Similarly, the protein content, amylose content and gel consistency under N2O2 were consistent with the rice quality under the N1O1 treatments above. In summary, optimizing organic fertilizer combined with urea practices was a win-win strategy to improve grain yield and quality while reducing CH4 emissions in the rice cropping system. This study provides new insights into the fertilizer types on CH4 emission and rice production of rice cropping systems.